Teaching Programming Students how to Model: Challenges & Opportunities - France, Robert (Electronic Communications of the EASST, 2012)
Computer Science students who have one or more years of basic programming experience and little or no exposure to abstractions above the code level, often struggle to grasp modeling concepts and practices in more advanced software development courses. In this talk I discuss some of the factors that contribute to this situation and propose a learning process in which the abstraction gap between models and implementations is gradually widened as student modeling skills are developed.